RANCANGAN SISTEM LAYANAN TERPADU (ONE STOP SERVICE) DENGAN PENDEKATAN KNOWLEDGE CAPTURE - Safrina Amini; Sri Mulyati; Noni Juliasari (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2012)
Processing student data currently spread across various systems that can only be accessed by the relevant working area(bureau) and authorities user. Constraints on the field then appeared at a particular official or staff to deal with customers in providing information related to the student data they need. The separation of access to information related to the system by the bureau become obstacles for such staff in the provision of information. So sometimes questions from customers only can be answered after the routing of requests for data or by way of calls to the bureau that has authority over related data. This results in a long service. This research will try to present a solution of the above problems. Through the knowledge capture approach, we will combine the data needs to be taken from the back end system as well as the tacit knowledge of the staff or officials usually interact directly in serving customers. The final results are expected in the form of a draft (prototype) one stop service system related to the presentation of data are often required students both in academic and non-academic of data.Keywords : Students Data, One Stop Service, Knowledge Capture